Pengamanan Citra Digital Terenkripsi Menggunakan Kombinasi Steganografi Bit Matching dan Kriptografi Cipher Feedback (CFB) dengan Pembangkit Bilangan Acak Linear Congruential Generator (LCG). - Widiastuti, Tiwuk (Jurnal Transformatika, 2023)
In this study, the design and manufacture of an encrypted digital image security system was carried out by combining bit matching steganography and cryptographic cipher feedback (CFB) using a linear congruential generator (LCG) as a key generator. The test material used 60 message images measuring 120x120 pixels with 1 cover image measuring 64x64 pixels. The results of the study were obtained: (1) the image can be hidden but there is an increase in the size of the embedding file with an average difference of 459.1167 KB (kilobytes) or an increase of 2135.65%, (2) The image can be reconstructed, the physical image of the extraction result is the same as the original image with an MSE value = 0, but there is a change in size that varies with an average difference of 3.433333 KB (kilobytes) or by 16.20%, (3) Some robust tests such as image rotation testing, brightness manipulation, addition of gaussian noise make the extracted image damaged. The image is resistant to all contrast tests. Salt and pepper noise testing does not damage the image too much, the image is still resistant to salt and pepper noise testing of 0.001 with an average MSE = 0